PENGARUH EFEKTIVITAS PENGENDALIAN INTERNAL DAN KETAATAN ATURAN AKUNTANSI TERHADAP KECENDRUNGAN KECURANAGAN AKUNTANSI PADA LPD DIKECAMATAN MENGWI - Ni Komang Sumadi; Ni Made Dewi Kansa Putri (UNHI Press, 2021)
The purpose of this study was to analyze the effect of the effectiveness of internal control and the obedience of accounting rules. This research was conducted in the LPD in Mengwi District, using the observation method, interview method, literature method, documentation method, and survey method by distributing questionnaires to LPD employees in Mengwi District. The research population was 310 employees. Determination of the sample using non probability sampling method with purposive sampling method. The research sample consisted of 76 employees. Data analysis using Multiple Linear Regression. The results showed that the effectiveness of internal control and compliance with accounting rules had an effect on the tendency of accounting fraud in the LPD in Mengwi District, which means that the higher the effectiveness of internal control, the better the management of financial statements so as to reduce the tendency for accounting fraud and compliance High accounting rules will affect the management of financial statements, the better and in compliance with applicable rules, it can reduce the tendency of accounting fraud, and vice versa.